A computer vision-based method for bridge model updating using displacement influence lines. (15th May 2022) - Martini, Alberto; Tronci, Eleonora M.; Feng, Maria Q.; Leung, Ryan Y.
Abstract: This paper presents a new computer vision-based method that simultaneously provides the moving vehicle's tire loads, the location of the loads on a bridge, and the bridge's response displacements, based on which the bridge's influence lines can be constructed. The method employs computer vision techniques to measure the displacement influence lines of the bridge at different target positions, which is then later used to perform model updating of the finite element models of the monitored structural system. The method is enabled by a novel computer vision-based vehicle weigh-in-motion method which the co-authors recently introduced. A correlation discriminating filter tracker is used to estimate the displacements at target points and the location of single or multiple moving loads, while a low-cost, non-contact weigh-in-motion technique evaluates the magnitude of the moving vehicle loads. The method described in this paper is tested and validated using a laboratory bridge model. The system was loaded with a vehicle with pressurized tires and equipped with a monitoring system consisting of laser displacement sensors, accelerometers, and cameras. Both artificial and natural targets were considered in the experimental tests to track the displacements with the cameras and yielded robust results consistent with the laser displacement measurements. The extracted normalized displacement influence lines were then successfully used to perform model updating of the structure. The laser displacement sensors were used to validate the accuracy of the proposed computer vision-based approach in deriving the displacement measurements, while the accelerometers were used to derive the system's modal properties employed to validate the updated finite element model. As a result, the updated finite element model correctly predicted the bridge's displacements measured during the tests. Furthermore, the modal parameters estimated by the updated finite element model agreed well with those extracted from the experimental modal analysis carried out on the bridge model. The method described in this paper offers a low-cost non-contact monitoring tool that can be efficiently used without disrupting traffic for bridges in model updating analysis or long-term structural health monitoring. Highlights: Non-contact computer vision-based methodology for extracting displacement influence lines. Simultaneous tracking of the bridge displacement, location and magnitude of the moving vehicle loads. Experimental validation with a laboratory bridge system and pressurized vehicle model. Excellent match between the simulated and experimental influence lines after model updating.